The Aesthetics of Historical Visual Storytelling in The "Cadet 1947" Film - Geofani, Jorgie; Yusril (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The movie "Cadet 1947" is about the struggle for Indonesian independence in the early days of the Republic, with a background of battles between the Dutch and Indonesian armies. In this movie, visual aesthetics are used to portray emotions and atmosphere relevant to Indonesian history. This research aims to analyze how the elements of visual aesthetics or mise en scene in the film "Cadet 1947". This research thoroughly explores the visual storytelling aesthetics in the film Cadet 1947 from a film studies perspective. The main focus of this research is the analysis of visual elements or Mise en scene such as settings, costumes, lighting, and actors, to convey the historical narrative of the AURI cadet struggle in 1947. This research uses a qualitative approach with literature study and filmography analysis. By exploring various cinematic and visual aspects, this article finds that Cadet 1947 effectively integrates aesthetic elements to strengthen the emotional and historical experience of the audience.